Rosacea in ophthalmological and dermatovenerologic practice. Clinical cases - P. E. Arsenyev; E. V. Orlov; A. A. Arsenyeva; Yu. M. Pakhomova (Российский офтальмологический журнал)
Rosacea is a chronic inflammatory disease that can manifest itself with various clinical symptoms. It is mainly a skin disease, but the eyes, including the eyelids, cornea and conjunctiva, can also be affected. Due to the variety of clinical manifestations of rosacea, including ocular forms, varying severity of the pathological process, as well as insufficient understanding of its etiology and pathogenesis, there are currently no universal treatment regimens. The purpose of the work is to substantiate a multidisciplinary approach to the treatment of this disease. Material and methods. This article considers the role of the Demodex mite in the development of the disease, various variants of its clinical manifestation, approaches to treatment, and two clinical cases. Results. The main treatment includes the use of both systemic and local drugs. In the treatment of ocular forms of the disease, in addition to systemic treatment, local agents are used, such as artificial tears, anti-inflammatory drugs and immunosuppressants. In cases of severe corneal damage, various types of keratoplasty may be required. Conclusion. To determine the most effective treatment strategy for cutaneous and ocular rosacea, collaboration between ophthalmologists and dermatologists is necessary.